2015
DOI: 10.15376/biores.10.2.3615-3624
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Air Flow Rate and Biomass Type on the Performance of an Updraft Biomass Gasifier

Abstract: Airflow and the type of biomass are the two most important factors influencing the performance of a biomass gasifier. In this research, the effects of air flow rate (air-fuel equivalence ratios of 0.21, 0.25, and 0.29) and biomass type (woody biomass, agricultural residue, and perennial grass) on the performance of an updraft biomass gasifier were evaluated based on its tar and producer gas generation. It was found that increasing airflow increased the formation of tar species for all biomass types studied, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Results pertinent to syngas composition indicate that the variation of CO as a syngas component with fuel moisture content is in line with studies performed by other researchers [8,[19][20][21]23]. Specifically, as fuel MC increases from 20% to 35%, CO concentration has a pronounced drop and this leads to a reduction in the syngas HHV.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results pertinent to syngas composition indicate that the variation of CO as a syngas component with fuel moisture content is in line with studies performed by other researchers [8,[19][20][21]23]. Specifically, as fuel MC increases from 20% to 35%, CO concentration has a pronounced drop and this leads to a reduction in the syngas HHV.…”
Section: Discussionsupporting
confidence: 88%
“…The H 2 content was found to have no significant changes while the CO content was somewhat reduced as the moisture content increased from 10% to 22% wb, resulting in a decrease in the higher heating value of the syngas from 3.67 to 2.84 MJ/m 3 . In a related study, James et al [23] found that as ER increased from 0.21 to 0.29, tar formation was raised from 1.6 to 3.1 g/m 3 for all types of biomass in their experiment, but there was no influence on syngas composition.…”
Section: Introductionmentioning
confidence: 83%
“…In this study, the mass yield of biochar for all biomasses was between 8% and 11%. These results are similar to those presented by James et al [44] who used a TLUD reactor at the laboratory scale and with the airflow rate of 20 L/min.…”
Section: Biochar Characterization As a Soil Amendmentsupporting
confidence: 90%
“…These results are similar to those presented by James et al . who used a TLUD reactor at the laboratory scale and with the airflow rate of 20 L/min.…”
Section: Resultsmentioning
confidence: 99%
“…The second stage was composed of two additional flasks submerged in dry ice (approximately´79˝C) at which most of the remaining tars was condensed. A similar method for tar collection was previously implemented [11,34,35]. A vacuum pump (Cole-Parmer, L-79200-30, Monroe, LA, USA) was used to flow the syngas within the tar sampling system, and a gas flow meter (Omega, PMR1-014697, Stanford, CT, USA) controlled the sampling rate at 10 lpm.…”
Section: Methodsmentioning
confidence: 99%